2021
DOI: 10.1101/2021.08.27.457903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated model for termination of RNA polymerase III transcription

Abstract: RNA polymerase III (RNAPIII) synthesizes essential and abundant non-coding RNAs such as tRNAs. Controlling RNAPIII span of activity by accurate and efficient termination is a challenging necessity to ensure robust gene expression and to prevent conflicts with other DNA-associated machineries. The mechanism of RNAPIII termination is believed to be simpler than that of other eukaryotic RNA polymerases, solely relying on the recognition of a T-tract in the non-template strand. Here we combine high-resolution geno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 64 publications
(81 reference statements)
2
14
0
Order By: Relevance
“…Metagene analysis of Pol III distribution around tRNA genes (Figure 4B) indicates that a considerable fraction of wild type Pol IIIs reads through the primary terminator (i.e. the first T-tract after the 3' end of the gene), in agreement with previous studies (Turowski et al, 2016;Xie et al, 2021). Importantly, we observed a significant increase in Pol III signal downstream of the primary terminator in the three mutants, indicating global transcription termination defects (Figure 4B and individual examples in Figure 4C).…”
Section: Pol III C128 Mutations Affect Yeast Viability and Cause Glob...supporting
confidence: 91%
See 3 more Smart Citations
“…Metagene analysis of Pol III distribution around tRNA genes (Figure 4B) indicates that a considerable fraction of wild type Pol IIIs reads through the primary terminator (i.e. the first T-tract after the 3' end of the gene), in agreement with previous studies (Turowski et al, 2016;Xie et al, 2021). Importantly, we observed a significant increase in Pol III signal downstream of the primary terminator in the three mutants, indicating global transcription termination defects (Figure 4B and individual examples in Figure 4C).…”
Section: Pol III C128 Mutations Affect Yeast Viability and Cause Glob...supporting
confidence: 91%
“…Instead, read-through (RT) products could be observed that corresponded to transcripts that were released once Pol III reached the end of the dsDNA. While our promoter-dependent transcription assay does not allow to distinguish between Pol III pausing and Pol III termination, a similarly prepared batch of purified Pol III could recently been shown to efficiently terminate on a 5-dT termination sequence on immobilized DNA templates (Xie et al, 2021). Together, these results confirmed that highly-purified Pol III is capable to pause, and presumably terminate, on its own in vitro on a poly-dT termination signal in a promoter-dependent transcription setup.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interactions of Sen1 with the replisome and RNAPIII are mutually exclusive, which implicates the existence of two distinct Sen1-containing complexes presumably with different functional roles. Interestingly, however, both interactions are impaired by the sen1-3 mutation, which likely alters a shared region of interaction (Xie et al, 2021). These findings indicate that the sen1-3 mutant allows untangling the function of Sen1 in NNS-dependent termination from its functions at the replisome and RNAPIII transcription.…”
Section: Introductionmentioning
confidence: 99%